Unveiling an Autonomously Functioning Thyroid Nodule: A Diagnostic Approach Using Thyroid Scintigraphy and HRUS of Thyroid - Rahman, Md Fuad Ruhani; Arna, Fahmida Kabir; Nadiruzzaman, Md (Bangladesh Journal of Nuclear Medicine, 2025)
Autonomously functioning thyroid nodule (AFTN) is one of the least common causes of hyperthyroidism. AFTN is a single hyper functioning thyroid nodule that is TSH independent and not controlled by the anterior pituitary gland or thyroid axis. As there are no tissue diagnostic criteria for AFTN, ultrasonography, scintigraphy, and biochemical assessments can evaluate AFTN. High-Resolution Ultrasound (HRUS) is recommended as the first-line modality in evaluating different types of thyroid nodules. Technetium-99m (Tc-99m) pertechnetate thyroid scintigraphy is a functional nuclear medicine study that uses a low level of radioactive tracer to assess the thyroid gland. The ensuing case is based on a 52-year-old male patient presenting with anterior neck swelling and neck pain who was referred to INMAS, Cox’s Bazar, for clinical evaluation. Bangladesh J. Nuclear Med. 27(2): 293-296, 2024